Sleep Behaviors in Persons With Alzheimer's Disease: Associations With Caregiver Sleep and Affect. (January 2022) - Mather, Molly A.; Laws, Holly B.; Dixon, Jasmine S.; Ready, Rebecca E.; Akerstedt, Anna M.
Poor sleep in persons with Alzheimer's disease (AD) is a common stressor for family caregivers. Retrospective reports support associations between sleep disturbance in persons with AD and worse caregiver mood; however, prospective associations between sleep in persons with AD and caregiver outcomes have not been studied. The current study determined associations between affect and sleep of persons with AD and their caregivers using daily diary data. Multilevel mediation models indicated that sleep in persons with AD is linked to caregiver affect; furthermore, these associations are mediated by sleep characteristics in caregivers and affect in persons with AD. Daily fluctuations in sleep behaviors in persons with AD—rather than average values—were most strongly associated with caregiver outcomes. Interventions to improve sleep in persons with AD may decrease their negative affect and improve caregiver mood.